The Neonatal Nurse's Role in Preventing Abusive Head Trauma - Allen, Kimberly A. (2014)
BACKGROUND: Abusive head trauma in infants occurs in 24.6 to 39.8 per 100,000 infants in developed countries. Abusive head trauma refers to any type of intentional head trauma an infant sustains, as a result of an injury to the skull or intracranial contents from a blunt force and/or violent shaking. CLINICAL QUESTION: What evidence-based interventions have been implemented by neonatal nurses to prevent abusive head trauma in infants? Search Strategy: PubMed was search to obtain English language publications from 2005 to May 2014 for interventions focused on preventing abusive head trauma using key terms ‘shaken baby syndrome’. SEARCH YIELD: A total of 10 studies were identified that met the inclusion criteria. All of the interventions targeted prevention of abusive head trauma with information about abusive head trauma/shaken baby syndrome and the ‘normal’ infant crying behaviors. MAIN FINDINGS: Interventions taught parents why infants cried, how to calm the infants, ways to cope with inconsolable infants, and how to develop a plan for what to do if they could not cope anymore. Parents who participated in the interventions were consistently able to explain the information and tell others about the dangers of shaking infants compared to the control parents. Only two studies calculated the pre-intervention abusive head trauma rate and the post-intervention frequency of abusive head trauma. Each found significant differences in abusive head trauma.